Exploring classroom community: A social network study of Reacting to the Past - Webb, Jeff; Engar, Ann (Teaching and Learning Inquiry, 2016)
In this exploratory social network study, we examined how student relationships evolved during three month-long Reacting to the Past (RTTP) role-playing games in a lower division honors course at a large US public university. Our purpose was to explore how RTTP games—and collaborative learning approaches more generally—impact classroom community in college courses. We found that both acquaintance and friendship ties between students increased dramatically during the game, eliminating student isolation without tending to create new cliques. These added ties made acquaintance and friendship networks simultaneously denser and more inclusive than they were before the game. We conclude by advancing a hypothesis about the network effects of intensive peer interaction. Collaborative learning approaches like RTTP, we suggest, produce high-density networks with limited clustering because structured peer interactions cut across existing or naturally occurring clique boundaries.